2015
DOI: 10.1016/j.cedpsych.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Refutations in science texts lead to hypercorrection of misconceptions held with high confidence

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
64
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 46 publications
12
64
5
Order By: Relevance
“…Two recent studies shed light on this objective. Evidence from van Loon, Dunlosky, van Gog, van Merriënboer, and de Bruin (2015) shows that confidence in misconceptions is not a sufficient condition for the backfire effect via refutation text. Rather, van Loon et al (2015) found that high confidence in science misconceptions that were the subject of refutation texts lead to hypercorrection, wherein refutation texts showed enhanced correction of high-confidence misconceptions compared with both expository texts and low-confidence misconceptions.…”
Section: Effects Of Self-concept In Controversial Knowledge Revisionmentioning
confidence: 96%
“…Two recent studies shed light on this objective. Evidence from van Loon, Dunlosky, van Gog, van Merriënboer, and de Bruin (2015) shows that confidence in misconceptions is not a sufficient condition for the backfire effect via refutation text. Rather, van Loon et al (2015) found that high confidence in science misconceptions that were the subject of refutation texts lead to hypercorrection, wherein refutation texts showed enhanced correction of high-confidence misconceptions compared with both expository texts and low-confidence misconceptions.…”
Section: Effects Of Self-concept In Controversial Knowledge Revisionmentioning
confidence: 96%
“…Tsai and Chang (2005) found that introducing discrepant and critical events to generate dissatisfaction with misconceptions was effective in promoting learning. Van Loon et al (2015) found that misconceptions held with high confidence were most effectively corrected by a combination of refutation text and correct text. In the words of Carsten-Conner et al (2015),…”
Section: Introductionmentioning
confidence: 99%
“…The sample of the pilot study consisted of one second (N = 20) and one fourth grade classroom (N = 15), with children in the same age as children at T 2 . The texts and questions we used in this pilot study were translated and adapted from studies by De Bruin et al (2011) and Van Loon et al (2015). Texts for fourth graders were longer and more complex, and questions were more difficult for fourth graders than for second graders.…”
Section: Pilot Studymentioning
confidence: 99%
“…Internal consistency of the true-false questions is rather low, however, low internal consistency is not uncommon for text comprehension tests (cf. Engelen et al 2018;Van Loon et al 2015). It lies in the very nature of metacognitive research that questions for which monitoring judgments are gathered, cover the entire variation of difficulty to allow tapping the whole range of monitoring processes.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation